A Digital Black Press?: Exploring What Constitutes the Black Press Online - Williams, Miya Christine (AoIR Selected Papers of Internet Research, 2016)
The traditional black press is typically conceptualized as legacy print publications that are produced by and for African Americans and that advocate for the race. Yet in the current digital environment, black-targeted websites that primarily produce entertainment news and sites that target African-American readers but are owned by white media companies create ambiguity. While research has been conducted on how mainstream publications have adapted to the digital landscape, this paper examines how that adaptation has occurred among black press outlets. This study investigates how producers and consumers of black news content online are troubling previous definitions of the black press. By examining how black news publishers of print and online content conceptualize their publications and how they are situated in the new media age, I am able to elucidate the affect that the changing digital landscape has on understandings of the black press.